Expression of fibulin‐5 in the skin of patients with rectal prolapse. (November 2015) - Joshi, H. M.; Gosselink, M. P.; Smyth, E. A.; Hompes, R.; Cunningham, C.; Lindsey, I.; Urban, J.; Jones, O. M.
Abstract Aim Components of connective tissue other than collagen have been found to be involved in patients with rectal prolapse. The organization of elastic fibres differs between controls and subsets of patients with rectal prolapse, and their importance for maintaining the structural and functional integrity of the pelvic floor has been demonstrated in transgenic mice, with animals which have a null mutation in fibulin‐5 (Fbln5¡/¡) developing prolapse. This study aimed to compare fibulin‐5 expression in the skin of patients with and without rectal prolapse. Method Between January 2013 and February 2014, skin specimens were obtained during surgery from 20 patients with rectal prolapse and from 21 without prolapse undergoing surgery for other indications. Fibroblasts from the skin were cultured and the level of fibulin‐5 expression was determined on cultured fibroblasts, isolated from these specimens by quantitative real‐time polymerase chain reaction. Immunohistochemistry was performed on fixed tissue specimens to assess fibulin‐5 expression. Results Fibulin‐5 mRNA expression and fibulin‐5 staining intensity were significantly lower in young male patients with rectal prolapse compared with age‐matched controls [fibulin‐5 mean ± SD mRNA relative units, 1.1 ± 0.41 vs 0.53 ± 0.22, P = 0.001; intensity score, median (range), 2 (0–3) vs 1 (0–3), P = 0.05]. There were no significant differences in the expression of fibulin‐5 in women with rectal prolapse compared with controls. Conclusion Fibulin‐5 may be implicated in the aetiology of rectal prolapse in a subgroup of young male patients.